2017
DOI: 10.1371/journal.pgen.1006876
|View full text |Cite
|
Sign up to set email alerts
|

A conserved mitochondrial surveillance pathway is required for defense against Pseudomonas aeruginosa

Abstract: All living organisms exist in a precarious state of homeostasis that requires constant maintenance. A wide variety of stresses, including hypoxia, heat, and infection by pathogens perpetually threaten to imbalance this state. Organisms use a battery of defenses to mitigate damage and restore normal function. Previously, we described a Caenorhabditis elegans-Pseudomonas aeruginosa assay (Liquid Killing) in which toxicity to the host is dependent upon the secreted bacterial siderophore pyoverdine. Although pyove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 76 publications
(95 reference statements)
5
57
0
Order By: Relevance
“…For example, we observed that methylcobalamin supplementation decreased acdh-1 expression by 10-fold or more while proportional increases were seen in resistance to propionate or P. aeruginosa in Liquid Killing. This result corroborates our recent findings that place mitochondrial homeostasis at the heart of this pathogenesis model (Tjahjono and Kirienko, 2017). Although the effect was smaller, benefits from B12 supplementation were still observed when stresses were more pleiotropic (such as heat shock or oxidative stress, where intracellular contents are more uniformly damaged).…”
Section: Discussionsupporting
confidence: 93%
“…For example, we observed that methylcobalamin supplementation decreased acdh-1 expression by 10-fold or more while proportional increases were seen in resistance to propionate or P. aeruginosa in Liquid Killing. This result corroborates our recent findings that place mitochondrial homeostasis at the heart of this pathogenesis model (Tjahjono and Kirienko, 2017). Although the effect was smaller, benefits from B12 supplementation were still observed when stresses were more pleiotropic (such as heat shock or oxidative stress, where intracellular contents are more uniformly damaged).…”
Section: Discussionsupporting
confidence: 93%
“…Utilizing iron chelators as chemical probes, they found that iron starvation is an important virulence determinant of P. aeruginosa in C. elegans. P. aeruginosa secretes the iron chelating siderophore pyoverdine, which disrupts mitochondrial homeostasis and induces a protective response in C. elegans that involves mitophagy [51] and the activation of innate immune defenses [52,53]. These data support previous studies [54,55], which demonstrate that C. elegans couple mitochondrial homeostasis to immune activation.…”
Section: Small Molecules As Chemical Biology Tools To Dissect Mechanisupporting
confidence: 84%
“…Compromising biofilm development by either genetic or chemical disruption severely decreased pyoverdine biosynthesis and rescued C. elegans from P. aeruginosa pathogenesis. Due to its roles in iron acquisition, regulation of secreted toxins such as the translational inhibitor ToxA and the protease PrpL, disruption of host mitochondrial function, and observations that compromising pyoverdine production is sufficient to rescue hosts from infection, pyoverdine is an important therapeutic target [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%